Upaya Pesantren Mempersiapkan Kemandirian Ekonomi Santri di Era Revolusi Industri 4.0: Studi Kasus di Pondok Pesantren Ar-Risalah Lirboyo Kota Kediri - Anis Humaidi (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2023)
This article discusses the breakthroughs made by Islamic boarding schools in order to equip students in the Industrial Revolution 4.0 era so they are not left behind in the economic field. Although the Ar-Risalah Lirboyo Islamic Boarding School still adheres to salafiyah teachings, this pesantren prepares its students to be able to survive in today's era. This paper will discuss the background of efforts to prepare student economic independence, the implementation of student independence preparation programs, and student readiness to face the Industrial Revolution 4.0. This research uses a qualitative approach with a case study type. In this study, data were obtained from two sources, namely humans and non-humans. Humans as informants in this study were caregivers, teacher, and students. While non-humans are documentation of Islamic boarding schools. The results of this study are caregivers who have a far-reaching vision to empower their students to live in their era. This vision is then realized by equipping students with IT teaching and mastery of foreign languages ??in the form of Arabic, English, Mandarin and Japanese. Apart from IT, students are also provided with life skill training. Ar-Risalah Islamic boarding school students are very ready to compete in the global world because they have mastered technology and foreign languages.